2012
DOI: 10.3109/03091902.2012.712201
|View full text |Cite
|
Sign up to set email alerts
|

Total duration of apnea and hypopnea events and average desaturation show significant variation in patients with a similar apnea–hypopnea index

Abstract: Obstructive sleep apnea (OSA) is commonly diagnosed based on the apnea-hypopnea index (AHI). Presently, novel indices were introduced for sleep apnea severity: total duration of sleep apnea and hypopnea events (TAHD%) and a combined index including duration and severity of the events (TAHD% × average desaturation). Two hundred and sixty-seven subjects were divided based on their AHI into four categories (normal, mild, moderate, severe OSA). In the most severe cases TAHD% exceeded 70% of the recorded time. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
(19 reference statements)
1
26
0
Order By: Relevance
“…The significantly larger amounts of upper airway closure during apnea events agree well with the definition of obstructive apnea and hypopnea 25,26 . The average duration was longer in hypopneic events compared with obstructive ones as described in the previous study by Muraja-Murro et al 27 . In addition to this, our results showed that the plateau percent during apneic events is larger compared with hypopneic ones, whereas the fluctuation was larger in hypopneic events.…”
Section: Discussionsupporting
confidence: 71%
“…The significantly larger amounts of upper airway closure during apnea events agree well with the definition of obstructive apnea and hypopnea 25,26 . The average duration was longer in hypopneic events compared with obstructive ones as described in the previous study by Muraja-Murro et al 27 . In addition to this, our results showed that the plateau percent during apneic events is larger compared with hypopneic ones, whereas the fluctuation was larger in hypopneic events.…”
Section: Discussionsupporting
confidence: 71%
“…58 Although obstruction severity tends to increase with a higher AHI, there is much variability and overlap in this parameter within mild, moderate, and severe AHI categories. 59 The heterogeneity in obstruction severity within similar AHI categories could reflect different arousal thresholds, with high arousal thresholds being associated with a diminished compensatory ventilatory response resulting in longer apneas with greater SpO 2 desaturation. 44 These parameters may offer more insight into the severity of OSA and deserve further study in populations undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Even individuals with the same AHI have vast differences in SDB characteristics. 9,10 Recent studies have highlighted that the oxygen-desaturation index (ODI) 11 or event duration 9,12 may be more predictive of cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%